Iron: copper interactions: some new revelations - Harris, E.D (Nutrition reviews, 1994)
Iron and copper show an uncommon but largely unexplained interdependence, the basis for which is being clarified in hemoglobin‐synthesizing cells, yeast, and photosynthetic microrgansims. The interactions of the two metals with membrane transport systems and genetic regulators are more apt to be cooperative than antagonistic.